Lessons in sustainable development from Malaysia and Indonesia - Hsu, Sara; Perry, Nathan, 1984- (Comparative studies of sustainable development in Asia., 2014)
"Sustainable Development in Malaysia and Indonesia" examines a range of topics pertaining to sustainable development in the two countries. While Indonesia and Malaysia are geographically close, Indonesia lags behind Malaysia in terms of well-being, with a lack of social services, and economic indicators, as GDP per capita is lower than that in Malaysia. Environmental problems are similar, since both possess large amounts of biodiversity and natural resources. Hsu and Perry provide a concise overview of sustainable development in the nations, make policy recommendations for each country, and discuss sustainable development experiments in both countries